Monitoring System for Organic Fertilizer Plant Controller Using Solar Energy. Issue 1 (June 2019) - Mardiyanto, Arief; Syamsul; Azhar
Abstract: In this applied research, a solar energy powered process control monitoring system of inorganic fertilizer plant with capacity of 300 liters has been developed. The process control system consists of PLC with solar energy panel as its power source and a monitoring process system. The monitoring process system includes a Raspberry Pi minicomputer, an LCD touchscreen, level shifter converters, Arduino Nano, RS485 modules, four analog sensors, and one digital sensor. This system works by collecting temperature, humidity, and gas concentrations data and controlling the heater, exhaust fan, and aerator to maintain desired processing conditions.DHT-22 digital sensor measures temperature and humidity, pH probe analog sensor measures pH values, MQ-4, MQ-7 and MiCS-2714 measures methane, carbon monoxide, and nitrogen dioxide gases respectively. Analog output sensor is read by PLC's analog to digital converter while digital output sensor is read by 1-wire bus by Arduino. The collected data is send over RS485 to Raspberry Pi. The plant temperature is set constant at 40°C. The heater is turned on at temperature of ≤ 38°C, when temperature reach ≤ 42°C the aerator, exhaust fan, and mixer will be on and will be switched off all together at 40°C. The temperature, humidity and PH are set as the reference of the control process.